ANALISIS NILAI TAMBAH ECENG GONDOK PADA KERAJINAN TANGAN DI DESA PANTAI HAMBAWANG KECAMATAN LABUAN AMAS SELATAN KABUPATEN HULU SUNGAI TENGAH(STUDI KASUS MUJISELA GALERY) - Aisyah, Lisda; Mubarak, Zaki; Amalia, Rizka (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
This research is motivated by water hyacinth which is considered a nuisance to community activities in the waters, especially people who make a living as fishermen. Then the water hyacinth is used for processing handicrafts. This aims to find out how much added value and benefits obtained from processing water hyacinth which initially did not have economic value into handicrafts that had economic value. The method used is descriptive quantitative method by conducting interviews, observation and recording. Data collection was carried out from January 21 to March 21, 2021. The analysis used was value added analysis using the Hayami method. The results of this study indicate that the average number of outputs produced in value added is 70Kg with the number of inputs is 80Kg, so as to get a conversion factor of 0.875. The workforce used is 5 HOK with a labor coefficient of 0.0625 HOK, and the added value generated from processing water hyacinth into handicrafts with bag products is Rp. 114,583.334/Kg with an added value ratio of 87.30% and a profit of Rp. .83,333,334/pcs with a profit rate of 68.73%.